2018
DOI: 10.1017/psrm.2018.18
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Economic Inequality: The Illusory Agreement

Abstract: Recent studies of attitudes toward economic inequality suggest that most people around the world prefer very low levels of inequality, despite well-known trends toward greater inequality within many countries. Even within countries, people across the political spectrum are said to be in remarkable agreement about the ideal level of economic inequality. Using survey data from 40 countries and a novel survey experiment in the United States, we show that this apparent agreement is illusory. When relying on a wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 50 publications
4
38
0
6
Order By: Relevance
“…Recently, Pedersen () demonstrated that unit effects may also affect people’s attitudes within the domain of politics. Similar to the temporal reframing used by Gourville, this study shows that people are less likely to accept a tax increase of US$420 per year than a – logically equivalent – tax increase of US$35 per month (Pedersen ; see also Pedersen & Mutz ).…”
Section: From Perceptions and Attitudes To Pecuniary Answerssupporting
confidence: 58%
See 2 more Smart Citations
“…Recently, Pedersen () demonstrated that unit effects may also affect people’s attitudes within the domain of politics. Similar to the temporal reframing used by Gourville, this study shows that people are less likely to accept a tax increase of US$420 per year than a – logically equivalent – tax increase of US$35 per month (Pedersen ; see also Pedersen & Mutz ).…”
Section: From Perceptions and Attitudes To Pecuniary Answerssupporting
confidence: 58%
“…Within cognitive psychology, Yamagishi () found, for example, that people perceived a disease to be riskier when the mortality rate was described as ‘1,286 out of 10,000 people’ than when it was described as killing ‘24.14 out of 100 people’. In general, unit effects seem to be a highly general phenomenon across domains (Denes‐Raj et al ; Pedersen & Mutz ). Recently, Pedersen () demonstrated that unit effects may also affect people’s attitudes within the domain of politics.…”
Section: From Perceptions and Attitudes To Pecuniary Answersmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between perceived and desired inequality may be due to heuristic processes, so that people anchor their responses on the current information available in their more immediate context (Tversky & Kahneman, 1974). For instance, people who were provided information about actual income inequality used it as an anchor to estimate the desired levels of inequality (Pedersen & Mutz, 2018). However, there is also evidence that supports a motivational component that leads people to justify their status quo (Jost & Banaji, 1994; van der Toorn & Jost, 2014).…”
Section: Existential Standards and Ideal Estimates Of Inequalitymentioning
confidence: 99%
“… 1. Pedersen and Mutz (2018) have shown that survey measures of pay preferences are highly affected by anchoring effects and ratio bias. These problems with the measures do not, however, undermine the finding that people would generally prefer to adjust the pay of politicians downward. …”
mentioning
confidence: 99%